90.3k views
3 votes
Solve −3x^2 − 4x − 4 = 0.

A) x equals quantity of 2 plus or minus 4i square root of 2 all over 3
B) x equals quantity of 2 plus or minus 2i square root of 2 all over 3
C) x equals quantity of negative 2 plus or minus 2i square root of 2 all over 3
D) x equals quantity of negative 2 plus or minus 4i square root of 2 all over 3

2 Answers

3 votes
x =(4-√-32)/-6=2/-3+2i/3√ 2 = -0.6667-0.9428i
x =(4+√-32)/-6=2/-3-2i/3√ 2 = -0.6667+0.9428i





User Wubin Ouyang
by
5.1k points
7 votes
For this case we have the following polynomial:

-3x^2 - 4x - 4 = 0
We apply the formula of the resolvent to solve the problem.
We have then:

x = (-b +/- √(b^2 - 4ac))/(2a)
Substituting values:

x = (-(-4) +/- √((-4)^2 - 4(-3)(-4)))/(2(-3))
Rewriting the equation we have:

x = (4 +/- √(16 - 48))/(-6)

x = (4 +/- √(-32))/(-6)

x = (4 +/- √(-2*16))/(-6)

x = (4 +/- 4i√(2))/(-6)

x = (-2 +/- 2i√(2))/(3)
Answer:
The roots of the polynomial are given by:

x = (-2 +/- 2i√(2))/(3)
C) x equals quantity of negative 2 plus or minus 2i square root of 2 all over 3
User Carry
by
5.4k points